A autorreflexão colaborativo-crítica como princípio para formação continuada: perspectivas para inclusão escolar - Silva, Fernanda Nunes da (2019)
This dissertation aimed to comprehend how the continuing education of education professionals, from a perspective of collaborative-critical self-reflection, with the intention of contributing to the process of school inclusion of the target audience of Special Education. Thereunto, it was fundamented in communicative action theory of Habermas and in the self reflective collaboration between researchers and participant professors proposed by Carr and Kemmis, also taking them as authors and investigators of their practice. From qualitative nature, collaborative-critical action research was assumed as investigative perspective with the other, whose realization happened through nonlinear movements of understanding and collaboration with the context. At the same time, it was sought to understand the processes of continuing education in its interface with Special Education in a municipal elementary school of Serra/ES and colaborate with the construction of a formative process by study-reflection group assuming the collaborative-critical self-reflection and the school inclusion as principles. Data production was based on instruments and strategies such as participant observation with register in field journaling, semi-structured interviews, semi-open quizzes, written narratives and dialogues established in the study-reflection group and at school. The data were organized from the content review and analyzed in the light of Habermas’ critical theory. Data analysis indicates that the conceptions of Special Education, school inclusion and continuing education present in the education professional’s speech, although still quite permeated by instrumental rationality, reveal a possible transition towards more critical and/or communicative perspectives. Professionals emphasized the necessity of a continuing education focused on the process of school inclusion, since the guarantee of reflection spaces and teacher education was, at that time, a challenge for the school organization. Thus, a study-reflection group was formed with professionals from this school, accepting the Special Education as a common interest from the perspective of school inclusion. The group was configured in a discursive space in which, through collaborative-critical self-reflection, it can rethink its own practices. The study shows that the reflection-study group has put itself as an alternative to the traditional models of teacher education and the collaborative-critical action research as a possibility of knowledge construction with the other, transforming conceptions and practices in favor of an inclusive school that favors everyone's learning. The educational product of this research presents a proposal for continuing education through study-reflection groups to guide and support the construction of other modes of education by education professionals in their own spaces.